PNe and H II regions in the starburst irregular galaxy NGC 4449 from LBT MODS data - Annibali, Francesca; Pasquali, Anna (Arxiv, 2017)
We present deep 3500$-$10000 $Å$ spectra of H II regions and planetary nebulae (PNe) in the starburst irregular galaxy NGC 4449, acquired with the Multi Object Double Spectrograph at the Large Binocular Telescope. Using the "direct" method, we derived the abundance of He, N, O, Ne, Ar, and S in six H II regions and in four PNe in NGC 4449. This is the first case of PNe studied in a starburst irregular outside the Local Group. Our H II region and PN sample extends over a galacto-centric distance range of $\appro